Severe adverse events impact overall survival and costs in elderly patients with advanced non-small cell lung cancer on second-line therapy. (May 2018) - Borghaei, Hossein; Yim, Yeun Mi; Guerin, Annie; Pivneva, Irina; Shi, Sherry; Gandhi, Mayank; Ionescu-Ittu, Raluca
Highlights: Severe adverse events (AE) are common during 2nd-line therapy for advanced non-small cell lung cancer (NSCLC). Severe AEs during 2nd-line therapy reduce median survival time by almost half. Severe AEs double healthcare costs during 2nd-line therapy. Abstract: Objectives: Elderly patients with advanced non-small lung cancer (aNSCLC) represent a high-risk patient population due to disease burden, comorbidities, and performance status, particularly after progressing on first-line therapy. Among elderly patients who receive second-line therapy, treatment related toxicities can have substantial impact on both clinical and economic outcomes. This study assessed the impact of severe adverse events (AEs) during second-line therapy on overall survival (OS) and all-cause heathcare costs in elderly with aNSCLC. Materials and methods: Patients with aNSCLC aged ≥65 years who initiated second-line chemotherapy/targeted therapy were identified in the SEER-Medicare database (2007–2011). Fifty-seven AEs were identified by literature review and consultation with two oncologists. Severe AEs were defined as AEs that required a hospitalization and were operationalized based on AE diagnosis(es) recorded during hospitalizations. OS post-second-line initiation and healthcare costs during second-line were compared between patients with and without severe AEs. Results: Among 3967 patients initiating second-line therapy, 1624 (41%) had ≥1 severe AE, where hypertension (26%), anemia (24%), and pneumonia (23%) were most commonly reported. Patients with and without severe AEs had similar demographic and cancer characteristics at diagnosis and similar second-line treatment regimens, but patients with severe AEs had more comorbidities at second-line initiation. Median OS was lower in patients with versus without severe AEs (6 vs. 11 months). After multivariate adjustment, hazard of death was more than twice higher in patients with versus without severe AEs (adjusted hazard ratio [HR] 2.31, 95% CI 2.16–2.47). Healthcare costs were more than twice higher in patients with versus without severe AEs ($16, 135 vs. $7559 per-patient-per-month). Conclusion: Severe AEs among elderly patients with aNSCLC treated with second-line chemotherapy/targeted therapy were found to be associated with decreased OS and increased healthcare costs. Results suggest a potential link between severe AEs in second-line treated aNSCLC elderly and patient survival and economic burden to the healthcare system.